Accuracy of heart girth for predicting live weight of Aceh cattle (Faculty of Animal Science, Universitas Brawijaya, 2014)
Data on live weight (LW) at 550 days of age and body measurements such as withers height (WH), body length (BL) and heart girth (HG) of Aceh bull and heifer have been collected from 79 animals (39 males and 40 females) managed at the Indrapuri’s Breeding and Forages Centre (IBFC) of Aceh Cattle, Indrapuri District, Aceh Besar Regency, Aceh Province, Indonesia to estimate the LW from body measurements. The overall means (+ SD) for LW, WH, BL and HG of Aceh cattle over sexes were 129.37 + 30.84 kg, 96.59 + 7.11 cm, 93.10 + 11.77 cm and 118.15 + 11.08 cm, respectively. The study revealed that HG was the best predictor of LW and this variable alone contributed 70% (female), 86% (male) and 74% (all animals) of the variation in the LW of Aceh cattle. It was concluded that highest determination coefficient (R2) value of simple linear regression model was found on model LW (kg) = -172.47 + 2.59HG (cm), whereas this model were more effective and efficient for predicting the LW of male Aceh cattle. Key words: Aceh cattle, body measurements, live weight estimation, regression models.